Types of Community Energy Use and Potential for Developing Biofuel Plants in The Bonehau Watershed - Muhammad Chairul S; Roland A. Barkey; Chairil A; Wardiman Mas'ud; Chaeria Anila; Marleny Dara; Muhammad Dahri Syahbani (JURNAL AGRIMENT, 2025)
Population growth is increasing beyond previous estimates. The world's energy needs are also extensive and continue to grow. This puts pressure on the energy available in nature in the form of biomass, and the decreasing fossil energy. So, alternative energy sources are needed that can be renewed in the form of Biofuel Sources. In addition, the development of biofuel energy source plants is a solution to restore environmental conditions. Based on this, it is necessary to identify the types of energy sources and the potential for developing biofuel energy source plants in the Bonehau Watershed ecosystem. The method used is non-experimental mapping based on Geographic Information Systems. The initial stage of introducing the identification of types of energy use by the community based on accessibility density classes. Furthermore, an analysis of the potential for developing biofuel plants, namely Nyamplung and Kemiri Sunan, was carried out using a land suitability approach. The Bonehau Watershed community generally uses LPG and firewood energy to meet household energy needs. Most people use more firewood energy than LPG because the watershed area has low accessibility, and the availability of firewood around the community's residence is limited. Analysis of Biofuel Plant Land Suitability in the form of Nyamplung Plants has the potential of 25% and Kemiri Sunan Plants 34% of the watershed area to be developed. The potential for developing these plants can handle 59% of the critical land for Nyamplung plants and 74% for Kemiri Sunan plants, from the total critical land area